Persepsi Wajib Pajak Orang Pribadi terhadap Tax Evasion di KPP Pratama Badung Utara - Wayan Bunga Larasati; Putu Wenny Saitri; Ni Putu Yuria Mendra (Jurnal Inovasi Akuntansi (JIA), 2023)
Taxes have a significant contribution to the Indonesian state. It is undeniable that one of the pillars of national income is derived from tax revenues, but currently the awareness of taxpayers in paying taxes is still low. Taxpayers think that taxes are a burden so that many taxpayers try to minimize the amount of tax owed by committing fraud, one of which is tax evasion.This study aims to determine the effect of tax understanding, tax audit, tax sanctions, tax rates, and the tax system on individual taxpayers' perceptions of tax evasion. The population of this study is individual taxpayers who are registered at North Badung KPP Pratama. The sample in this study were 100 people who were obtained based on the accidental sampling method. The analysis technique used is multiple linear regression analysis technique. The results of the analysis show that tax understanding has no effect on individual taxpayer perceptions of tax evasion, while tax audits, tax sanctions, tax rates, and the tax system have a positive effect on individual taxpayer perceptions of tax evasion. Future researchers are expected to be able to use the Google form to be more effective and efficient in data collection and are expected to be able to use other variables to explain the effect of individual taxpayer perceptions on tax evasion.